2006
DOI: 10.1016/j.atmosenv.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Flow reactor studies of the stable carbon isotope composition of secondary particulate organic matter generated by OH-radical-induced reactions of toluene

Abstract: Secondary particulate organic matter (POM) formed in a flow reactor by the OH-radical-induced reactions of toluene was collected on quartz fiber filters, and its stable carbon isotope ratio was analyzed by off-line combustion and subsequent dual-inlet isotope ratio mass spectrometry. The toluene consumption in these experiments ranged from 7% to 29%. The stable carbon isotope composition (i5 13 q of the secondary POM was in the range of -32.2%0 to -32.9%0 (VPDB scale), with some indication for a slight depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 27 publications
1
66
0
Order By: Relevance
“…More recently it also has been suggested that compound specific isotope ratio measurements can be used to study the formation of secondary organic pollutants from VOC degradation in the atmosphere (Irei et al, 2006(Irei et al, , 2011Irei, 2008, Fisseha et al, 2009Li et al, 2010;Iannone et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently it also has been suggested that compound specific isotope ratio measurements can be used to study the formation of secondary organic pollutants from VOC degradation in the atmosphere (Irei et al, 2006(Irei et al, , 2011Irei, 2008, Fisseha et al, 2009Li et al, 2010;Iannone et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the kinetic isotope effect and mass budget considerations the products of toluene oxidation in the initial phase of the reaction will be 5 ‰-6 ‰ lighter than the parent compound. Indeed, Irei et al (2006) observed that secondary POM formed by the OH-radical initiated oxidation of toluene in a flow reactor is on average 5.6 ‰ lighter under conditions where less than 30 % of toluene has reacted (Fig. 4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Rudolph (2007) has demonstrated that isotope fractionation can occur during reactions of volatile organic compounds with oxidants. Few studies have examined isotope fractionation during SOA formation (Irei et al, 2006;Fisseha et al, 2009;Irei et al, 2011). Wang and Kawamura (2006) showed that aging removes lighter carbon isotopes from particulate phase in the atmospheric oxidation processes.…”
mentioning
confidence: 99%